Layers as epistemic and political devices in mobile locative media; the case of iNakba in Israel/Palestine. Issue 1 (2nd January 2021) - Musih, Norma; Fisher, Eran
ABSTRACT: At the centre of this article is iNakba, a digital navigational application created by a Tel Aviv-based NGO in 2014. The app superimposes a layer of ruined Palestinian localities destroyed following the 1948 war, on top of the established and hegemonic Israeli geographical representation. At the end of this war and with the formation of the State of Israel, the presence of these localities was eradicated from both the territory and Israeli maps. The iNakba app uses Google maps and Waze as platforms for allowing users to find these localities and navigate towards them in order to increase knowledge about the repressed geographical past of the territory and bring about a political change. By examining iNakba from a media practice perspective, and by comparing it to a printed map published almost seven decades earlier and in very different circumstances, we highlight the unique role of layers in constructing and deconstructing cartographical knowledge. Layers, we argue, allow new potentialities for the representation and imagination of space, specifically, problematizing the eradication of Palestinian localities from the map and suggesting to re-imagine the territory as comprising the two histories and the two peoples. More broadly, the article suggests to understand layers as both a technical and political device.